The Impact of Trunk Rotation Movements on Increased Muscle Tone and Functional Movements for Patients after Stroke - Vaida Vaišvilaitė; Brigita Zachovajevienė; Pavelas Zachovajevas; Jonas Poderys (Lithuanian Sports University, 2020)
Experienced stroke causes malfunction not only in arm or leg movements, but also the ability to manage torso posture and complete torso movements performed by the torso muscles. Abnormal muscle tone is one of the stroke damage areas. The most common residual effects of stroke are paresis, spasticity and functional movement disorder. Muscle tone regulation acts as a relevant task for the theory and practice of physical therapy. This paper investigates the most effective method of increased muscle tone and its reduction for patients after stroke. It also provides a methodology which could be fully benefited by the entire rehabilitation team. Aim of research: to define the impact of trunk rotational movements on increased muscle tone and functional movements for patients after stroke. The study included patients after stroke and those who had increased muscle tone. The same patients received two means of decreasing the muscle tone: the 1st one based on the trunk rotational movements, the 2nd - stretching exercises for the limbs. The research focused on muscle tone of: flexor carpi radialis, biceps brachii, gastrocnemius and quadriceps femoris. The effectiveness of physiotherapy was assessed by evaluating the change in muscle tone using a Myoton-3 tone meter. Moreover, a change in functional movements before and after physiotherapy was evaluated using Rivermed's scale for movement assessment. Evaluation group consisted of 15 patients (n = 15). Conclusions: 1. Trunk rotation movements statically significantly decrease an increased muscle tone of: flexor carpi radialis, biceps brachii, gastrocnemius and quadriceps femoris (p < 0.05) 2. The average change in muscle tone for trunk rotation movements was statically significantly higher using the method of trunk rotational movements than using stretching exercises (p < 0.05). 3. Both, trunk rotational movements and stretching exercises, improve the functional movements (p < 0.05), however, trunk rotational movements have a higher impact than stretching exercises (p < 0.05). 4. Trunk rotational movements decrease muscle tone and improve functional movements for patients after stroke (p < 0.05). Keywords: stroke, hypertonus, decreased spasticity.